Modern Disinformation and Its Socio-Security Connotation - Anđelković, Slobodan M.; Lazić, Željko V.; Milašinović, Miraš S. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
The contemporary world faces disinformation as a primary challenge, given its capacity to undermine both social stability and national security. The digital political environment— shaped by advanced technologies and social media platforms—enables disinformation to spread more rapidly than traditional propaganda, introducing a range of uncertainties into public discourse. The main research objective is to examine how disinformation affects public trust and political authority, as well as its function as a strategic tool in domestic control and international hybrid warfare. The study begins with a theoretical exploration of disinformation as a phenomenon of social and political communication, integrating insights from security studies, political science, and media theory. The analysis highlights the transformation of information systems—from truth-based knowledge structures to digital environments where multiple narratives, algorithmic filtering, and selective framing dominate public discussions. Disinformation reshapes political landscapes by fostering echo chambers, which fragment communities and erode institutional trust. This analysis draws on academic literature, official reports, and targeted case studies. The 2016 U.S. presidential election and the global COVID-19 pandemic are presented as key examples illustrating how disinformation campaigns influence public attitudes and political decision-making. Findings indicate that state agencies, non-state actors, political organizations, and digital platforms often collaborate in the dissemination of disinformation. Evidence suggests that such operations are strategically planned and executed to achieve political or economic goals, thereby generating social instability and threatening national security. One of the paper’s conclusions is that disinformation poses multifaceted threats across various sectors of society. Its proliferation diminishes public confidence in official institutions, while simultaneously increasing reliance on alternative information sources that may propagate falsehoods. Disinformation also serves as a hybrid warfare instrument, allowing armed forces to target adversaries through information operations rather than conventional military engagement. The rise of artificial intelligence has increased the danger of sophisticated fake content development, enabling the rapid creation of deepfakes and synthetic texts. Disinformation campaigns transcend international borders and operate outside established legal frameworks. The expansion of major technology companies and their algorithmic control over information distribution complicates governmental efforts to safeguard national information spaces. Furthermore, the widespread tendency toward confirmation bias fosters belief systems rooted in personal prejudice, prompting individuals—most often online—to seek environments that reinforce their views. These factors collectively facilitate the spread of disinformation and hinder efforts to counter it. The current era confronts two critical disinformation threats: the erosion of factual knowledge and the destabilization of social stability and national security. The continued evolution of disinformation technologies creates conditions in which information control may become a central mechanism of political power, potentially giving rise to techno-authoritarian regimes. Safeguarding the right to free and truthful information, while effectively managing malicious content, demands an integrated approach grounded in democratic principles.